What indication, morbidity and mortality for central pancreatectomy in oncological surgery? A systematic review. (April 2016) - Santangelo, Michele; Esposito, Anna; Tammaro, Vincenzo; Calogero, Armando; Criscitiello, Carmen; Roberti, Giuseppe; Candida, Maria; Rupealta, Niccolò; Pisani, Antonio; Carlomagno, Nicola
Abstract: Conventional pancreatic resections for pancreatic neck and body diseases include pancreaticoduodenectomy, distal pancreatectomy with or without splenectomy, and total pancreatectomy. Recent studies have reported encouraging results of non-traditional pancreatic resections, including central pancreatectomy (CP), for central pancreatic disease. This surgical approach offers the potentials of low postoperative morbidity and preservation of metabolic functions. This study performs a systematic review on CP. A comprehensive literature search was conducted, for the period 1992–2015, on three worldwide databases: PubMed, Scopus, ISI-Web of Knowledge. We focused on indications, morbidity and mortality of this surgical procedure. The review shows that CP is particularly suitable for small-medium size diseases localized into the pancreatic body. This procedure is associated with an increased postoperative morbidity but an excellent postoperative pancreatic function. CP is a safe and effective procedure when performed following the right indications.